Effectiveness of Competency and Potential Assessment Services for ASN in the Technical Implementation Unit of the Center for Employee Assessment - Amelia Kusuma Dewi; Magda Faradiba (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This study aims to analyze the effectiveness of competency and potential assessment services for Civil Servants (ASN) at the Technical Implementation Unit of the Employee Assessment Center (UPT PPP) of the East Java Provincial Civil Service Agency. Competency assessment is a strategic instrument in ASN talent management that requires optimal service quality to support career development and bureaucratic professionalism. This study uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews with assessment participants, and questionnaires. Data analysis refers to the five dimensions of service quality according to Parasuraman, including Tangible (Physical Evidence), Reliability, Responsiveness, Assurance, and Empathy. The results of the study show that the services of the PPP Technical Implementation Unit are generally considered good, especially in terms of the professionalism of the assessors, the friendliness of the team, and the adequacy of physical facilities. However, the effectiveness of services still needs to be improved through the strengthening of an early information system, improvements in technological infrastructure, improvements in facilities and infrastructure such as adjustable chairs and internet stability, and transparency in the assessment process. This study provides recommendations to strengthen schedule management and dissemination of the assessment system so that services can be more effective and contribute optimally to the development of ASN competencies.